Proposed integrated cash Waqf investment model for micro enterprise in Malaysia: An empirical analysis - Duasa, Jarita; Mohd Thas Thaker, Mohamed Asmy (Center for Islamic Philanthropy and Social Finance (CIPSF), Universiti Teknologi MARA, Malaysia, 2017)
Micro Enterprises (MEs) in Malaysia becomes as an important engine for economic growth. Despite its importance and the continuous support from the government, MEs in Malaysia are facing some problems. Several earlier studies stated that Malaysian MEs face the problem of accessing finance due to many factors. Malaysian government has introduced and continued to assist Small and Medium Enterprises (SMEs) through the implementation of several policies, programmes and extensive financial resources allocations to enhance the activities of SMEs. However, these efforts have not been adequate to meet the needs of micro enterprises. The objectives of this study are: 1. To discuss the extent of the problems of (i) financing, (ii) human capital (iii) market accessibility (iv) innovation and technology adoption, and (v) infrastructure development faced by MEs in Malaysia. 2. To develop an alternative model that is available for effectively addressing the problems mentioned in (1) and 3. To analyze the probability that MEs will adopt the proposed model (cash waqf investment model). In methodology, primary data are collected using self-developed questionnaire (survey) This study focuses on MEs in Klang Valley (Selangor and Kuala Lumpur) since it records the highest number of such enterprises in the area. The analysis is conducted using statistical analysis and Logistic Regression analysis. The study finds that high probability of MEs opting for the proposed Integrated Cash Waqf model for their business financing is contributed by the high business annual turnovers, older entrepreneurs, those who have more awareness on cash waqf and those who have experienced applying loan recently.